2015
DOI: 10.1163/19552629-00802004
|View full text |Cite
|
Sign up to set email alerts
|

Give-Constructions in Heritage Ambon Malay in the Netherlands

Abstract: The domains where languages show variable syntax are often vulnerable in language contact situations. This paper investigates one such domain in Ambon Malay: the variable encoding ofgive-events. We studygive-expressions in the Ambon Malay variety spoken by heritage speakers in the Netherlands, and compare the responses of heritage speakers with those of homeland speakers in Ambon, Indonesia. We report that heritage Ambon Malay shows an innovative higher incidence ofdoconstructions compared to the homeland vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Because structural priming also occurs between languages, the idea of structural priming as a mechanism of language change can of course also take place between languages, potentially leading to contact-induced language change (cf., Fernández et al 2017;Loebell and Bock 2003;Kootstra and Doedens 2016;Kootstra and Muysken 2017;Kootstra andŞahin 2018;Travis et al 2017). Contact-induced language change can be defined here as (probabilistic) differences in linguistic preferences between speakers that have been frequently using another language as well, compared to speakers that have not (e.g., Dogruöz and Backus 2009;Indefrey et al 2017;Moro and Klamer 2015;Otheguy et al 2007;Villerius 2019). Indeed, consistent with the hypothesized link between contact-induced change and cross-linguistic priming, Fernández et al (2017) observed that Spanish-English bilinguals were more tolerant than monolinguals in their judgments of L1 language structures that contained innovations from their L2, and that these results could be linked to other results in this population of bilinguals, in which they observed priming of innovative language use across languages.…”
Section: Priming and Language Changementioning
confidence: 99%
“…Because structural priming also occurs between languages, the idea of structural priming as a mechanism of language change can of course also take place between languages, potentially leading to contact-induced language change (cf., Fernández et al 2017;Loebell and Bock 2003;Kootstra and Doedens 2016;Kootstra and Muysken 2017;Kootstra andŞahin 2018;Travis et al 2017). Contact-induced language change can be defined here as (probabilistic) differences in linguistic preferences between speakers that have been frequently using another language as well, compared to speakers that have not (e.g., Dogruöz and Backus 2009;Indefrey et al 2017;Moro and Klamer 2015;Otheguy et al 2007;Villerius 2019). Indeed, consistent with the hypothesized link between contact-induced change and cross-linguistic priming, Fernández et al (2017) observed that Spanish-English bilinguals were more tolerant than monolinguals in their judgments of L1 language structures that contained innovations from their L2, and that these results could be linked to other results in this population of bilinguals, in which they observed priming of innovative language use across languages.…”
Section: Priming and Language Changementioning
confidence: 99%
“…The aim of this study is to investigate the association between the structural divergence in various areas of heritage Ambon Malay grammar and social-psychological factors in order to account for the variability observed in the heritage speaker population. The data on structural divergence are based on previous work on heritage Ambon Malay (Moro, 2014, 2016, 2017; Moro & Klamer, 2015).…”
Section: The Study: Social-psychological Factors and Linguistic Divermentioning
confidence: 99%
“…This article examines the role of social-psychological factors in the development of Ambon Malay in the Netherlands, a heritage language spoken by Moluccan immigrants and their descendants (see the section Ambon Malay in the Netherlands ). Due to the intense contact with Dutch, the dominant language of the country, and to the restricted domains of usage (typically the home), heritage Ambon Malay has come to diverge significantly from its homeland variety and has adopted a number of Dutch-like features (Aalberse & Moro, 2014; Huwaë, 1992; Moro, 2014, 2015, 2016, 2017; Moro & Irizarri van Suchtelen, 2017; Moro & Klamer, 2015; Tahitu, 1989; see also the section Structural features ).…”
Section: Introductionmentioning
confidence: 99%
“…Heritage speakers of Ambon Malay are bilingual in Dutch and Ambon Malay, but have Dutch as their dominant language. Previous studies (Aalberse & Moro, 2014;Huwaë, 1992;Lekawael, 2011;Moro, 2014;Moro & Klamer 2015;Tahitu, 1989) have shown that Ambon Malay in the Netherlands is undergoing a substantial number of changes owing to unbalanced bilingualism in general, and to the intense contact with Dutch in particular.…”
Section: Introductionmentioning
confidence: 99%